Miltefosine implementation for treatment of cutaneous leishmaniasis: access indicators in the state of Minas Gerais, 2021-2024 - Sarah Nascimento Silva; Mell Ferreira Saliba; Laís Raquel Ribeiro; Gláucia Cota (Epidemiologia e Serviços de Saúde)
Abstract Objective To describe and evaluate the initial indicators of the pilot implementation of miltefosine in Minas Gerais for the treatment of cutaneous leishmaniasis. Methods This is a descriptive, cross-sectional study based on regulatory documents and secondary administrative data generated during the dispensing of miltefosine in Minas Gerais between May 2021 and April 2024. Indicators related to access and operability of the strategy implemented were calculated for the steps involved in approving the request for use and dispensing of the drug. Results The authorization rate was 97.5% for 281 valid requests. The outpatient clinic of the René Rachou Institute, a reference center for leishmaniasis in Minas Gerais, was responsible for the largest number of requests during the period. The health macro-regions Centre and North concentrated the largest number of requests (48.9% and 33.6%), which coincided with the regions with the highest number of reported cases. Median time for analyzing requests and for the person to access the medicine was 1.0 (0-76) and 10.0 (0-340) days, with significant variation between the health macro-regions. One hundred and nineteen people were treated in a municipality other than their place of residence. Of these, 49 needed to travel to another health macro-region. The miltefosine diffusion rate was 11.3% for the three-year period monitored, with significant variation between the macro-regions. Conclusion The indicators confirmed that miltefosine has been implemented, but revealed low diffusion and regional disparities. Barriers need to be identified and strategies developed to expand equitable access to new technologies.